1992
DOI: 10.1021/bi00139a003
|View full text |Cite
|
Sign up to set email alerts
|

Antigen binding thermodynamics and antiproliferative effects of chimeric and humanized anti-p185HER2 antibody Fab fragments

Abstract: The murine monoclonal antibody 4D5 (anti-p185HER2) inhibits the proliferation of human tumor cells overexpressing p185HER2 in vitro and has been "humanized" [Carter, P., Presta, L., Gorman, C. M., Ridgway, J. B. B., Henner, D., Wong, W.-L. T., Rowland, A. M., Kotts, C., Carver, M. E., & Shepard, H. M. (1992) Proc. Natl. Acad. Sci. U.S.A. (in press)] for use in human cancer therapy. We have determined the antigen binding thermodynamics and the antiproliferative activities of chimeric 4D5 Fab (ch4D5 Fab) fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
55
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 32 publications
10
55
0
Order By: Relevance
“…This is in agreement with earlier results (42) and with the functional affinities determined for the monoclonal antibody humAb4D5-8 (24) and the 4D5 Fab fragment (70). In all of these measurements the soluble recombinant HER-2-ECD was used, whereas the RIA experiments were performed on whole cells.…”
Section: Comparison Of Binding Kinetics By Surface Plasmonsupporting
confidence: 92%
“…This is in agreement with earlier results (42) and with the functional affinities determined for the monoclonal antibody humAb4D5-8 (24) and the 4D5 Fab fragment (70). In all of these measurements the soluble recombinant HER-2-ECD was used, whereas the RIA experiments were performed on whole cells.…”
Section: Comparison Of Binding Kinetics By Surface Plasmonsupporting
confidence: 92%
“…, which were previously reported for various antigen-antibody associations (28,29,35,37,38,40,41,(43)(44)(45). In general, the negative ⌬Cp values for protein folding and protein-ligand association are proportional to the reduction in water-accessible nonpolar surface areas of the molecules, and related to the contribution of hydrophobic effect to molecular association (13)(14)(15)(16)51).…”
supporting
confidence: 61%
“…Recently this method has been applied to the quantitative thermodynamic analyses of antibody binding to various types of antigens, e.g. haptens (28 -31), oligosaccharides (32)(33)(34), and proteins (35)(36)(37)(38)(39)(40)(41)(42)(43)(44). However, no calorimetric studies have been reported on the antigen-antibody interaction in affinity maturation.…”
mentioning
confidence: 99%
“…Production and purification of rhuMAbHER2, rhuMAbHER2.Fab, and NRG1 177-244 -poly-L-lysine conjugates We used a humanized recombinant HER2 Ab (rhuMAbHER2), 36 its Fab product (rhuMAbHER2.Fab), 37 or the EGF-like domain of NRG1 (NRG1 177-244 ) 38 as the basis for our gene transfer vehicles. These agents allowed us to characterize the utility of targeting the HER2 molecule in a monovalent versus bivalent fashion (rhuMAbHER2.Fab versus rhuMAbHER2) or NRG1 binding sites (HER3 homodimers, HER4 homodimers, and HER2/HER3 or HER2/HER4 heterodimers).…”
Section: Resultsmentioning
confidence: 99%
“…The humanized HER2 Ab (rhuMAbHER2), 36 the Fab of this Ab (rhuMAbHER2.Fab), 37 and the EGF-like domain of NRG1 (NRG1 177-244 ) 38 have been described previously. Poly-L-lysine polymers (pLYS) of different chain lengths (158 and 251 lysines) were obtained from Sigma (St. Louis, Mo).…”
Section: Preparation Of Poly-l-lysine Dna Complexesmentioning
confidence: 99%